2021
DOI: 10.3389/fmicb.2021.662785
|View full text |Cite
|
Sign up to set email alerts
|

Debaryomyces hansenii Strains Isolated From Danish Cheese Brines Act as Biocontrol Agents to Inhibit Germination and Growth of Contaminating Molds

Abstract: The antagonistic activities of native Debaryomyces hansenii strains isolated from Danish cheese brines were evaluated against contaminating molds in the dairy industry. Determination of chromosome polymorphism by use of pulsed-field gel electrophoresis (PFGE) revealed a huge genetic heterogeneity among the D. hansenii strains, which was reflected in intra-species variation at the phenotypic level. 11 D. hansenii strains were tested for their ability to inhibit germination and growth of contaminating molds, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 67 publications
(96 reference statements)
1
18
0
Order By: Relevance
“…However, what we observed is a noticeable decrease or even an absence of apparent sporulation in the treated plates. This fact has been previously mentioned in other studies, but as far as we know, and in relation to the use of D. hansenii , neither quantitative data nor images supporting the proposal were provided [ 20 , 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, what we observed is a noticeable decrease or even an absence of apparent sporulation in the treated plates. This fact has been previously mentioned in other studies, but as far as we know, and in relation to the use of D. hansenii , neither quantitative data nor images supporting the proposal were provided [ 20 , 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 78%
“…The latter are specifically associated with inhibition of germination and mycelial growth of Candida and Penicillium species. [ 29 ]. To our knowledge, our research is the first report that specifically shows images of how the diffusible and volatile compounds’ action affects sporulation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, fewer microorganisms can stand the high osmotic pressure or need more time to adapt their metabolism to the high salt amounts, giving D. hansenii the advantage to grow. The second case has been already appointed by several authors who demonstrated that D. hansenii produces a killer toxin (mycocin) only in the presence of NaCl (Huang et al, 2021;Llorente et al, 1997;Marquina et al, 2001;Medina-Córdova et al, 2018). This toxin seems to be effective against different genres of yeast, fungi and bacteria.…”
Section: Discussionmentioning
confidence: 94%
“…Other yeast species ( Candida maltosa , D. hansenii , I. orientalis , P. occidentalis , M. guilliermondii , M. caribbica , K. marxianus ) have been later tested in vitro against grain-spoiling fungi such as P. citrinum , P. chrysogenum , P. roqueforti , and P. verrucosum [ 66 , 69 , 70 , 106 , 107 ]. In most instances, the biological efficacy of volatile compounds was measured on vegetative growth or spore germination ( Table 1 ).…”
Section: Vocs-mediated Control Of Postharvest Mycotoxigenic Fungimentioning
confidence: 99%
“…Only Alasmar et al [ 70 ] reported a significant reduction (from 31.1 ± 0.54 μg/kg in the control, to 0.12 ± 0.03 μg/kg in the exposed fungus) of OTA released in the medium by P. verrucosum upon exposure to K. marxianus volatiles. The volatile components considered responsible for fungal growth or mycotoxin inhibition were: isoamyl acetate, isoamyl alcohol [ 66 ], 2-methyl-1-propanol, 3-methyl-1-butanol, 2-methyl-1-butanol [ 106 ], 2-phenylethanol [ 69 , 107 ], phenylethyl acetate [ 69 ], nonadecane, eicosane, docosane, heptacosane, hexatriacontane, and tetracosane [ 70 ] acetone [ 107 ], as well as several esters, alcohols, terpenes, ketones, aldehydes, and aromatic hydrocarbons [ 69 ].…”
Section: Vocs-mediated Control Of Postharvest Mycotoxigenic Fungimentioning
confidence: 99%